Please Join Me/Us/Them on My/Our/Their Journey to Justice in STEM. Issue 5 (3rd July 2022) - Roscoe, Rod D.
ABSTRACT: Despite decades of effort to broaden participation in science, technology, engineering, and mathematics (STEM), many fields remain demographically skewed. Marginalized and minoritized people are still underrepresented in and underserved by the sciences. In this paper, the author considers the question, "How do we improve representation in STEM?" by reflecting on his own journey and themes such as imposter syndrome, decentering, meritocracy, and activism. Importantly, "underrepresentation" is not a mysterious happenstance but rather a predictable outcome of systemic inequity and systematic exclusion. By attending to the mechanisms of oppression, we can enact interventions that address root causes instead of symptoms. There are multiple ways that our research, teaching, and practice might change "the system" by making inclusion and equity the focus of our work, applying these principles to frame research questions and interpret findings, and adopting methods and practices that are inclusive and equitable.